I just need help >.<
I cant solve this I just need someone to help me.
I just need help >.<
I cant solve this I just need someone to help me.
The easiest way to find the inverse of a function in my opinion is to first change the f(x) back into y and swap your x's and y's. Doing these things gives you:
x = 6y + 11. After you do this simply solve for y and your answer will be the inverse.
start by substracting 11 on both sides of the equation then divide both sides by 6. this should give you y = (x-11)/6
Let's rewrite the function notation by using "y" term.
ƒ(x) = 6x + 11
y = 6x + 11 , let's solve this equation for "x"
6x = y - 11
x = (1/6) y - 11/6
Now, switch the "x" and "y"
y = (1/6) x - 11/6
In function notation:
ƒ^{ - 1}(x) = (1/6) x – 11/6
Inverse fucntions are symmetric with respect to line y=x. Mathematically it can be written as
f(g) = x
where g(x) is the inverse to f(x) (g = f^{-1}). But
f(g) = 6g +11 and thus 6g + 11 = x. Hence it follows g(x) = (x-11)/6
Comments
Agreed Xavier. Except at the very end, you should use f^{-1}(x) = ... instead of y = ... and of course in slope intercept form you have, f-1(x) = (1/6)x - (11/6)
kim
Correct. I typed the solution right before I began a session with a student so I had to speed things up a little therefore I didn't display the best use of notation.
Comment